On the Value of Considering Specific Facets of Interactional Justice Perceptions - Fouquereau, Evelyne; Morin, Alexandre J. S.; Huyghebaert, Tiphaine; Chevalier, Séverine; Coillot, Hélène; Gillet, Nicolas (Frontiers in Psychology, 2020)
This research seeks to verify the value of considering specific perceptions of interpersonal and informational justice over and above employees’ global perceptions of interactional justice. In Study 1, we examined the underlying structure of employees’ perceptions of interactional justice at work by contrasting first-order and bifactor representations of their ratings. The results showed that employees’ perceptions of interactional justice simultaneously reflected a global overarching interactional justice construct, together with two specific dimensions (interpersonal and informational justice). Study 2 examined latent profiles of employees based on their global (interactional justice) and specific (interpersonal and informational justice) levels of interactional justice. The results revealed five distinct interactional justice profiles related to employees’ levels of anxiety and emotional exhaustion.